The Relevance of Ibn Khaldun’s Economic Thought in the Contemporary World - Siti Kholifatul Rizkiah; Abdelkader Chachi (Türkiye İslam İktisadı Dergisi)
Ibn Khaldun’s economic thought, in his phenomenal book Al-Muqaddimah (The Prolegomenon), has been the subject of interest for many social scientists, including some economists of our era. He is considered to be among the early Muslim scholars, who wrote about the fundamental theories of economic science, three centuries before Adam Smith, who is widely regarded as the ‘father of economics’. However, six hundred years after Ibn Khal- dun’s death, a question arises as to whether his economic thoughts are still relevant in the contemporary world. This paper attempts to analyse some of the main economic theories of Ibn Khaldun and reviews whether they are still relevant or being discussed in the modern economic theory or applied in the economic practice. The study found that from amongst the six main economic thoughts, he wrote about in his book, Al-Muqaddimah, almost all are still widely used and practiced. However, his theory on money needs more deliberate research and further investigation, as the world has long replaced gold and silver money with fiat money and other kinds of currencies such as cryptocurrencies, which were not known at his time.